Posterior hippocampal regional cerebral blood flow predicts abstinence: a replication study. (11th January 2016) - Adinoff, Bryon; Harris, Thomas S.; Gu, Hong; Stein, Elliot A.
Abstract: The posterior hippocampus (pHp) plays a major role in the processing and storage of drug‐related cues and is linked to striatal‐limbic brain circuits involved with craving and drug salience. We have recently reported that increased basal regional cerebral blood flow (rCBF) in a pHp loci, as measured by pseudo‐continuous arterial spin labeling magnetic resonance imaging, predicted days to cocaine relapse following residential treatment. In this secondary analysis, we explored whether rCBF in this same pHp region would successfully predict 30‐day point prevalence abstinence 60 days following residential treatment in an independent group of previously studied participants with cocaine dependence. rCBF was assessed with single photon emission computerized tomography during a saline infusion in 21 cocaine dependence and 22 healthy control participants. pHp rCBF was significantly higher in those endorsing substance use ( n = 10) relative to both abstinent ( n = 11) ( p < 0.001) and control ( p < 0.05) participants. There were no significant differences in measured demographic or clinical variables between the actively using and non‐using participants. This replicative finding suggests that heightened pHp activation is a significant predictor of substance use in cocaine‐dependent individuals, possibly reflecting a neural susceptibility to continued drug cues. Abstract : The posterior hippocampus (pHp) is linked to striatal‐limbic circuits involved with craving. We recently reported increased pHp ASL‐assessed basal regional cerebral blood flow (rCBF) predicted days to cocaine relapse following residential treatment. In this secondary analysis, increased pHp rCBF (by single photon emission computerized tomography) successfully predicted 30‐day point prevalence substance use 60 days following residential treatment in an independent group of cocaine‐dependent participants. This replicative finding that suggests heightened pHp activation predicts future substance use, possibly reflecting a neural susceptibility to drug cues.